Mechanical Characteristics of Pineapple Leaf Fiber and E-Glass Hybrid Composites as an Alternative for Boat Hulls - Mohammad Arbeel Falaah; Amir Marasabessy (Applied Science and Technology on Naval Engineering, 2026)
The transition toward sustainable and eco-friendly materials in the maritime sector has accelerated research intonatural fiber-reinforced composites as potential alternatives to conventional structural materials. This study rigorouslyevaluates the mechanical characteristics of a hybrid sandwich composite structure, strategically incorporatingPineapple Leaf Fiber (PALF) as the core and E-Glass fiberglass as the outer skins. The composite matrix utilizes anepoxy resin modified with 1 gram of Aerosil nanofiller to enhance interfacial adhesion and resin viscosity. To optimizethe fiber-matrix compatibility, the PALF was subjected to varying concentrations of alkaline treatment using SodiumHydroxide (NaOH) solutions at 0%, 5%, 10%, and 15% for a duration of 2 hours. The fabrication of the test specimenswas conducted using the hand lay-up method, ensuring uniform resin distribution and minimizing void formation.Comprehensive mechanical characterizations were performed, including tensile testing in accordance with the ASTMD3039 standard and flexural testing following the ASTM D7264 standard.The experimental results unveiled a distinct bell-shaped performance curve for tensile strength relative to the NaOHconcentration. The optimal Ultimate Tensile Strength (UTS) was achieved at the 10% NaOH variation, recording apeak value of 77.33 MPa. This substantial enhancement is attributed to the optimal delignification process, whichincreased fiber surface roughness and promoted mechanical interlocking without damaging the cellulose structure.Conversely, the 15% NaOH treatment led to a significant degradation of the cellulose microfibrils, plummeting theUTS to 34.00 MPa. In contrast, the flexural test results demonstrated that the maximum Ultimate Flexural Strength(UFS) occurred in the untreated (0% NaOH) variation at 115.00 MPa, with the 10% NaOH variation closely followingat 108.33 MPa. This behavior indicates that the flexural properties of the sandwich composite are predominantlygoverned by the high-stiffness E-Glass outer skins rather than the core material. Finally, the structural viability of thecomposites was assessed against the stringent regulations established by the Indonesian Bureau of Classification (BKI)for small-to-medium fiberglass boat hulls, which mandate a minimum tensile strength of 43.12 MPa. The findingsconfirm that only the 10% NaOH treated hybrid composite successfully surpasses this regulatory threshold, renderingit a highly promising and sustainable alternative material for marine hull construction.